The Initial Condition of Legal Consciousness of Pedagogical College Students - NAZKHANOVA, Galiya; KHAN, Natalya; ABDULLAYEVA, Gulzira; KALIMOLDAYEVA, Ardak; ABDRAKHMANOV, Asan (Journal of Advanced Research in Law and Economics; Vol 9 No 8 (2018): JARLE Volume IX Issue 8(38) Winter 2018DO - 10.14505//jarle.v9.8(38).17, 2019)
Legal consciousness of a man is formed during the whole period of his life-sustaining activity. Thus, students define legal consciousness as an aggregate synergetic effect on professional environment. Novelty of the paper is grounded by authors with the fact that within research structure the key basis is represented not with the strategy of legal consciousness formation as a result of pedagogic experiment but with definition of its initial values and, subsequently, development of methods aimed at its correcting. Thus, authors determine the initial values bear rating character and along with this have impact on programs of students' legal consciousness formation upon development of new education standards and implementation of regulatory documents. In addition, author suggest that the basis for legal consciousness development is the formation of flexible strategy of legal consciousness level increase that will provide full integration of the present aspect into legal framework of teaching process and formation of personal interest of students in development of professional competence of their future learners.